The association of periodontal disease and cardiovascular disease risk: Results from the Hispanic Community Health Study/Study of Latinos. Issue 7 (20th July 2018) - Singer, Richard H.; Stoutenberg, Mark; Feaster, Daniel J.; Cai, Jianwen; Hlaing, WayWay M.; Metsch, Lisa R.; Salazar, Christian R.; Beaver, Shirley M.; Finlayson, Tracy L.; Talavera, Gregory; Gellman, Marc D.; Schneiderman, Neil
Abstract: Background: Current evidence suggests that periodontal disease (PD) is associated with a significant increased risk of atherosclerotic cardiovascular disease (CVD) independent of known confounders. PD is a chronic oral disease with significant variation in prevalence demonstrated among Hispanic/Latino subgroups. The purpose of this study was to investigate the associations between PD and CVD risk and variations with sex, age, and Hispanic/Latino background. Methods: The sample included 7379 participants aged 30 to 74 years, from the Hispanic Community Health Study/Study of Latinos (2008 to 2011). We assessed CVD risk by the Framingham 10‐year general CVD risk score (FGRS). PD severity classification was based on calibrated measurements of gingival recession and probing depth. Multivariable sequential linear models for complex sample design assessed FGRS by PD severity, Hispanic/Latino background, and covariates. Results: The prevalence of moderate and severe PD combined was 46%. For women and men with severe PD, the combined prevalence of moderate and high CVD risk was 44% and 85%, respectively. The FGRS observed for women (5.1% [95% CI: 4.1%, 6.0%], p < 0.001) and men 10.8% (95% CI [9.2%, 12.3%], p < 0.001) with severe PD were 56% and 134% greater than those without PD, respectively. Dominican women and men with moderate or severe PD, aged 60 to 69 years, exhibited the greatest CVD risks (FGRS = 15.1%, 95% CI [7.8%, 22.5%]) and (FGRS = 40.2%, 95% CI [30.2%, 50.3%]), respectively. Conclusions: Moderate and severe PD were associated with significant CVD risk with marked sex disparity and heterogeneity by Hispanic/Latino background.